Leader’s Implicit Followership and Employees’ Innovative Behavior: Chain Mediation Effect of Leader–Member Exchange and Psychological Empowerment - Liang, Wei; Lv, Chen; Yu, Yongchang; Li, Tingyi; Liu, Peng (Frontiers in Psychology, 2022)
In the Chinese society, where power distance is high, leaders’ attitudes and behavior toward employees determine their career development as well as affect the entire team’s performance. Therefore, exploring the kind of employees that leaders expect in China is essential. Based on implicit followership theory perspective, this study considers leaders’ positive implicit followership (LPIF) as the main research variable and examines its influence on employees’ innovative behavior (EIB). Moreover, it explores the multiple mediation effect of the leader–member exchange (LMX) relationship and psychological empowerment (PE) in this influence mechanism. The study sample comprised 389 leaders and their direct employees at 45 large- and medium-sized enterprises in Shandong, Beijing, Hebei, Shanghai, Shanxi, Zhejiang, and other regions of China. We used the leader–employee 1:1 matching questionnaire, and the longitudinal research design was adopted to avoid homology variance, making the study results more realistic and reliable. This study used the SPSS 26.0 and AMOS 26.0 statistical software to verify the hypotheses. Our findings show that LPIF has a significant positive effect on EIB, and LMX and PE have multiple mediation effects on the relationship between LPIF and EIB. When the level of LPIF is high, LMX and PE are also enhanced, which in turn promotes the increase in EIB. This study provides a new perspective for subsequent research on the psychological mechanism of employees and suggests an important method for understanding leadership and following processes in an organization. It plays a guiding role for the management practice of an enterprise, selection of leaders, and training of employees.